Hematologic predictors of mortality in hospitalized patients with COVID-19: a comparative study. Issue 1 (1st January 2020) - Mousavi, Seied Asadollah; Rad, Soroush; Rostami, Tahereh; Rostami, Mohammadreza; Mousavi, Seyed Ali; Mirhoseini, Seied Amirhosein; Kiumarsi, Azadeh
ABSTRACT: Background : The first cases of proved COVID-19 in Iran were reported in February 2020 and has since rapidly spread worldwide. We aimed to clarify the clinical significance of hematologic parameters alteration in COVID-19. Methods : Different hematologic parameters were measured in 225 hospitalized COVID-19 patients in a tertiary care university hospital, during the peak of COVID-19 outbreak and their association with duration of hospitalization, ICU admission and especially mortality was analyzed. Results : Among a total of 225 patients, 24.4% did not survive after admission. Lymphopenia and neutrophilia were observed in 52.7% and 21.4% of the patients, respectively. The mean count of neutrophils was significantly higher in non-survived patients ( P = .032). Elevated neutrophil-to-lymphocyte ratio (NLR) was significantly associated with mortality ( P < .001). Low hemoglobin (Hb) concentration significantly correlated with mortality ( P = .004) and ICU admission ( P = .04). Platelet (Plt) count was significantly lower in the non-survived patients ( P = .023). Non-survivors had significantly lower nadir Hb and Plt counts than survivors ( P < .001 in both parameters). Platelet-to-lymphocyte ratio (PLR) also correlated with mortality and was significantly higher in non-survivors ( P = .034). Conclusions : Hematologic laboratory parameters have always been a crucial component of diagnostic and therapeutic strategies in infectious disease. Hematologic predictors of a fatal outcome in COVID19 hospitalized patients in our series include elevated NLR and PLR, lower than normal Hb and Plt, elevated d -dimer and prolonged prothrombin time (PT), together with elevated inflammatory indicators in the blood.